PENETAPAN LOKASI BERJUALAN OLEH PEDAGANG MAKANAN KELILING DI KECAMATAN TAMPAN KOTA PEKANBARU - ", Melisa; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The topic of this study is the Determination of Selling’s Location of Food Peddlers in Tampan Sub-District, Pekanbaru, by the problems of (1) How is the determination of selling location of food peddlers in Tampan? (2) What is the relationship between the types of merchandise and the selling facilities with the selling location determination? The purpose of this study is to find out how the location of selling food vendors in Tampan is determined and to find out whether there is a relationship between merchandise types and selling facilities with selling locations. This research is descriptive quantitative research. The data were collected by using incidental sampling techniques and data collection using observations and questionnaires. The sample of this research was 49 food peddlers. The results showed that 40.8% of food peddlers determined the educational environment as a selling location, the 26.5% in housing and boarding houses. And 32.7% determined the location of selling in recreational parks. The determination of the selling location was determined by the movement and distribution of food peddlers in peddling their merchandises. The peddlers who do a lot of movement and distribution are ice cream peddlers which are as much as 10.2%. Most of the peddlers used motorcycles as the transportation by the percentage of 73.5% with the help of sound system as the selling media by the percentage of 67.3%.Keywords: Street vendors, Food Peddlers, Tampan